2018
DOI: 10.1007/s00289-018-2492-x
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium oxide–carbon-based nanofiller-reinforced conducting polymer nanocomposites and their supercapacitor applications

Abstract: In this review article, we have presented for the first time the new applications of supercapacitor technologies and working principles of the family of RuO 2-carbon-based nanofiller-reinforced conducting polymer nanocomposites. Our review focuses on pseudocapacitors and symmetric and asymmetric supercapacitors. Over the last years, the supercapacitors as a new technology in energy storage systems have attracted more and more attention. They have some unique characteristics such as fast charge/discharge capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 146 publications
0
9
0
Order By: Relevance
“…), or a conductive polymer such as PANI, PPy, etc. 116,117 RuO 2 is highly pseudocapacitive, yielding 90% charges stored through the oxidation−reduction reaction during the charge−discharge process, and the rest by the EDLC type of storage. The improvement can be attributed to the mixed ion/ electronic pathway.…”
Section: Metal Oxide-based Supercapacitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…), or a conductive polymer such as PANI, PPy, etc. 116,117 RuO 2 is highly pseudocapacitive, yielding 90% charges stored through the oxidation−reduction reaction during the charge−discharge process, and the rest by the EDLC type of storage. The improvement can be attributed to the mixed ion/ electronic pathway.…”
Section: Metal Oxide-based Supercapacitorsmentioning
confidence: 99%
“…), or transition metal oxides (TiO 2 , SnO 2 , MnO 2 , Co 3 O 4 , etc. ), or a conductive polymer such as PANI, PPy, etc. , …”
Section: Metal Oxide-based Supercapacitorsmentioning
confidence: 99%
“…Incorporating inorganic or organic fillers into the polymer matrix is a fascinating method for improving the mechanical, tribological, thermal, and/or electrical properties of the polymer matrix. Over the past few decades, the tribological or other properties of filler-incorporated epoxy composites have been widely investigated. Research studies show that many kinds of microfillers/nanofillers, including TiO 2 , Al 2 O 3 , polytetrafluoroethylene, graphite, MoS 2 , and so forth, are able to effectively improve the tribological or mechanical properties of the epoxy matrix. By preparation of micro- and nano-TiO 2 -incorporated epoxy composites, Jochheim demonstrated that the TiO 2 nanoparticles imparted a better wear resistance to the epoxy matrix than the TiO 2 microparticles, mainly attributed to the fact that the nanosized TiO 2 had a higher surface area originating from the small size effect, thereby inducing a stronger interfacial interaction between nano-TiO 2 and the epoxy matrix.…”
Section: Introductionmentioning
confidence: 99%
“…As reinforcements, different microfillers in the shape of fibers [ 1 , 2 , 3 ], powders [ 4 , 5 ], or nanofillers [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ] are used. Metal particles, ceramic powders or fibers, and natural fibers are widely applied as reinforcements as well.…”
Section: Introductionmentioning
confidence: 99%